Taxonomic review of the Oriental genus Gandhara Moore with descriptions of four new species (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Černý, Karel; Huang, Si-Yao; Hu, Hua-Lin (Zootaxa, 2023)
The genus Gandhara Moore, 1878 is reviewed. Four new species are described: Gandhara typica Volynkin & Černý, sp. n. (Nepal, northeast India, northern Myanmar and northern Thailand), Gandhara clava Volynkin & Černý, sp. n. (Laos and northern Thailand), Gandhara emgai Volynkin & Černý, sp. n. (northern Vietnam), and Gandhara interrogativa Volynkin, Černý, S.-Y. Huang & H.-L. Hu, sp. n. (northern Vietnam and southern China). Gandhara typica sp. n. is fixed as the type species of the genus Gandhara whereas Lithosia serva Walker, 1854 considered by authors as the type species of Gandhara by misidentification is transferred to the genus Collita Moore, 1878. Two new combinations are introduced: Gandhara conica (Fang, 2000), comb. n. and Collita serva (Walker, 1854), comb. n. A lectotype is designated for Lithosia serva Walker, 1854 in order to stabilise the nomenclature. Adults as well as male and female genitalia are illustrated.